Effectiveness of radiofrequency and exercise-based rehabilitation on symptoms associated with pelvic floor dysfunction in breast cancer patients: A study protocol - Cristina Salar-Andreu; Sergio Montero-Navarro; Ana Lozano-Rubio; Sonia Del Rio-Medina; Jose M. Botella-Rico; María Torres-Lacomba; Josep C. Benítez-Martínez; Jesús Sánchez-Más; Cristina Orts-Ruiz (PLoS ONE, 2025)
Background Breast cancer is currently the most diagnosed type of cancer in the world, with a five-year survival rate of 90%. Survivors develop genitourinary dysfunction symptoms due to cancer treatment, which implies that they have to endure physical and psychological sequelae, with a negative impact on their quality of life. We present a study protocol to verify the effect of radiofrequency (RF) and pelvic floor muscle training (PFMT) for the treatment of genitourinary dysfunction in breast cancer survivors. Methods/Design This is a double-blind, three-arm, randomised clinical trial (Registration: NCT06694519). Participants from two breast cancer associations from Alicante (Spain) will be randomly assigned to one of the three intervention groups (RF, PFMT, RF + PFMT). It will include survivors aged ≥ 18 years who present pelvic dysfunction assessed by the Pelvic Floor Distress Inventory questionnaire (PFDI20) ≥ 100. Pelvic muscle strength, pelvic function, vaginal symptoms, sexual function, self-esteem and quality of life will be evaluated before the intervention, with follow-up at 15 days, 6 months and 1 year after the intervention. Expected results RF could offer additional benefits to PFMT due to its proven effectiveness in the treatment of vaginal dryness and dyspareunia. The expected results will have a positive impact on the health and well-being of women with breast cancer, reducing the symptomatology associated with the disease and its treatment, and improving their quality of life, as well as providing value for the development of more effective treatment protocols. Trial registration ClinicalTrials.gov NCT06694519